Factors Influencing Indonesian Generation Z in Choosing Job: Twitter Analytics Studies - Adrian Azhar Wijanarko (University of Merdeka Malang, 2024)
Generation Z is the generation born between early 2000 and mid-2010. Currently, this generation group has entered the job market and will control it for the foreseeable future. Finding workers from generation Z is a crucial step in ensuring the organization's sustainability. As a result, this study looks at the aspects that Generation Z considers while making a job decision. In contrast to earlier studies, this one makes use of big data analysis with interview to explain reason. The main source of data is conversational data from social media Twitter. Participants in this study ranged in age from 19 to 25. During the 15 days of data collection, a total of 10,531 conversations were collected with the majority of which came from the island of Java. According to the study's findings, 62% of generation Z respondents sought that recognition was important to them when seeking for a job. With a conversation percentage of 26%, work environment are the second most sought-after component in the workplace. Meanwhile, the factors of flexibility, independence and transparency have a value of less than 10% of the total conversation on social media known as Twitter.